EARLIEST TRIASSIC CONODONTS FROM CHITRAL, NORTHERNMOST PAKISTAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Extensive tracts of very shallow water carbonates in the valleys of the Yarkhun and Mastuj rivers of Chitral (northernmost Pakistan) previously though to be Permian (or Cretaceous) are shown by conodonts from two horizons in sequences 110 km apart—near Torman Gol (Mastuj valley) and near Sakirmul (upper Yarkhun valley)—to include earliest Triassic (Scythian—Induan) horizons. Both faunas have Isarcicella staeschei Dai & Zhang, Is. lobata Perri, Is. turgida (Kozur et al.) and Hindeodus parvus (Kozur & Pjatakova), whereas Is. Isarcica (Huckriede) has been recognised only in the Torman Gol occurrence. The presence, respectively, of Is. staeschei in the Sakirmul and Is. isarcica in the Torman Gol occurrences, allows discrimination of the staeschei and isarcica zones respectively the third and the fourth conodont biozones of the Early Triassic conodont biozonation of Perri (in Perri & Farabegoli 2003). Such faunas, consisting mainly of isarcicellids and hindeodids but lacking gondolellids, are characteristic of restricted sea environments across the Permian–Triassic boundary and in the earliest Triassic in other Tethyan areas. The conodont faunas from these two occurrences are remarkably similar, nearly contemporaneous, and indicate shallow water biofacies. They are inferred to equate with the Ailak Dolomite, a sequence of Late Permian–?Late Triassic dolostones discriminated farther up the Yarkhun valley and extending eastwards into the upper Hunza region of northernmost Pakistan. The Zait Limestone and Sakirmul carbonate sequence are consistent with extension of the previously inferred Triassic carbonate platform at least 110 km farther to the SW than previously supposed.